Faktor Risiko Penyebaran Escherichia coli Penghasil ESBL pada Ternak Ayam Komersial - Wibisono, Freshinta Jellia (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Escherichia coli producing ESBL in humans, animals and the environment trigger the emergence of antimicrobial resistance. This study analyzes the potential risk factors in commercial chickens as an infectious factor for the ESBL-producing Escherichia coli as an effort to prevent and control the wider spread of Escherichia coli-producing ESBL events. This study was a descriptive analytic epidemiological study with a cross-sectional study design. Sampling using stratified random sampling by taking as many as 5 samples per commercial chicken farm in Blitar District. Data collection is done by direct interviews with farmers based on a questionnaire and field observations and inspection of livestock, supplemented with supporting documentation. Primary data were obtained through a questionnaire and direct observation of the research object to determine risk factors that could affect the Escherichia coli producing ESBL that were resistant to antibiotics in commercial chicken in Blitar District. Escherichia coli is a commensal bacterium that is naturally present in the chicken digestive tract. The existence of the highest ESBL producing Escherichia coli was 45.56% in the type of partnership farming. Risk factors with the highest association strength on risk factors for partnership type (OR = 11.02, CI 95% = 5.84-20.77), the presence of antibiotic administration programs (OR = 6.76, 95% CI = 2.05-22.22), broiler chicken species ( OR = 5.34, 95% CI = 2.76-10.32), and the purpose of using antibiotics as prevention (OR = 3.55, 95% CI = 1.86-6.74). Efforts to prevent and control the ESBL-producing Escherichia coli in commercial poultry can be done by increasing surveillance of antibiotic use, in this regard it is necessary to supervise animal health personnel in the management of livestock raising for the correct use of antibiotics in commercial chicken farms.